Arctiin protects against cardiac hypertrophy through inhibiting MAPKs and AKT signaling pathways - Jing Li; Yu-Pei Yuan; Si-Chi Xu; Ning Zhang; Chun-Ru Xu; Chun-Xia Wan; Jie Ren; Xiao-Feng Zeng; Qi-Zhu Tang (Elsevier, 2017)
Purpose: The mitogen-activated protein kinases (MAPKs) and protein kinase B (AKT) pathways have emerged as essential intracellular signaling pathways in eukaryotic cells, particularly as regulators of cardiac hypertrophy. Previous studies indicated that arctiin, an active ingredient of biennial dried ripe burdock, could exhibit potent anti-inflammatory and anti-allergic activities via down-regulating the activation of MAPKs and AKT pathways. However, little is known about its effects on cardiac hypertrophy. Therefore, the present study aimed to explore whether arctiin could attenuate cardiac hypertrophy. General methods: Arctiin (80 mg/kg) was administered by oral gavage once daily for 3 weeks from 1 week after surgery. Then, the mice were subjected to either chronic pressure overload generated by aortic banding (AB) or sham surgery (control group). Cardiac function was assessed by echocardiography. Findings: The results indicated that arctiin attenuated cardiac hypertrophy induced by AB, and suppressed cardiac fibrosis and accumulation of collagen in vivo. Arctiin also inhibit the activation of MAPKs and AKT occurs in response to hypertrophic stimuli. Arctiin attenuated phenylephrine-induced hypertrophy of myocytes in vitro. Conclusions: In conclusion, arctiin can improve cardiac function and prevent the development of cardiac hypertrophy by blocking the MAPKs and AKT signaling pathways.